(untitled) (Research, Society and Development, 2021)
The present study aimed to verify the influence of breastfeeding on children’s oral and systemic health, verifying children’s hospitalization, use, indication and type of antibiotics used. This is a cross-sectional longitudinal study with a sample of 42 children at 30 months of age. The logistic regression test was used at a significance level of 5% for statistical analysis. Among the children, 64.28% had already been weaned before reaching 6 months of age; 11.90% had caries lesion. Simplified Oral Hygiene Index (OHI-S) was performed in 38 children, from which 92.10% had regular OHI-S and 07.90% had poor OHI-S. Of the 42 children, the indication for antibiotics use was 50% for pharyngitis, 28.83% for pneumonia, 08.33% for cold, 04.17% for sinusitis, 04.17% for bronchitis, 04.17% for stomatitis, 04.17 % for virus and 04.17% for ocular cellulitis. In this study, there was no relationship between early weaning, oral health conditions, hospitalization and antibiotics use. Presence of caries in early childhood was found in 11.90% of children. All children presented unsatisfactory OHI-S and there was no relationship between this variable and the others. Much of the indication for the use of antibiotics was for the treatment of respiratory tract infections, with beta lactams being the most used.